Tourism Object Development Model Based on Traditional Village in Apuan Village, Bangli District - Ni Made Puspasutari Ujianti; Ni Made Sukaryati Karma; Ida Ayu Putu Widiati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Tourism has several forms, one of which is community-based tourism. Community-Based Tourism, or what is often referred to as Community Based Tourism (CBT) is a form of tourism managed by local communities with an emphasis on environmental, social, and cultural sustainability principles to help tourists understand and learn the local community's way of life. CBT aims to build and strengthen organizational capabilities in local communities. CBT prioritizes improving the welfare of the community through the empowerment of tourism village development which is carried out based on the potential of the rural community itself. Likewise, Apuan Village, Susut District, Bangli Regency, which is rich in potential spiritual tourism objects such as the Tirta Payuk tourist attraction in the Banjar Bangunlemah Kangin, Yeh mangsi, and Tirta Empul attractions in the Banjar Apuan. However, the problem then is that the utilization of tourism objects in Apuan Village has not been maximized. In this study, the object of study to be studied is Apuan Village by emphasizing the model of tourism object development by analyzing the potential and characteristics of Apuan Village so that later an appropriate tourism object development model can be arranged so that it can be applied optimally.